Effects of hesperidin in orange juice on blood and pulse pressures in mildly hypertensive individuals: a randomized controlled trial (Citrus study) - Valls, Rosa M. (Eur J Nutr, 2020)
PURPOSE: To assess the sustained and acute effects, as well as the influence of sustained consumption on the acute effects, of orange juice (OJ) with a natural hesperidin content and hesperidin-enriched OJ (EOJ) on blood (BP) and pulse (PP) pressures in pre- and stage-1 hypertensive individuals. METHODS: In a randomized, parallel, double-blind, placebo-controlled trial, participants (n = 159) received 500 mL/day of control drink, OJ, or EOJ for 12 weeks. Two dose–response studies were performed at baseline and after 12 weeks. RESULTS: A single EOJ dose (500 mL) reduced systolic BP (SBP) and PP, with greater changes after sustained treatment where a decrease in diastolic BP (DBP) also occurred (P < 0.05). SBP and PP decreased in a dose-dependent manner relative to the hesperidin content of the beverages throughout the 12 weeks (P < 0.05). OJ and EOJ decreased homocysteine levels at 12 weeks versus the control drink (P < 0.05). After 12 weeks of EOJ consumption, four genes related to hypertension (PTX3, NLRP3, NPSR1 and NAMPT) were differentially expressed in peripheral blood mononuclear cells (P < 0.05). CONCLUSION: Hesperidin in OJ reduces SBP and PP after sustained consumption, and after a single dose, the chronic consumption of EOJ enhances its postprandial effect. Decreases in systemic and transcriptomic biomarkers were concomitant with BP and PP changes. EOJ could be a useful co-adjuvant tool for BP and PP management in pre- and stage-1 hypertensive individuals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00394-020-02279-0) contains supplementary material, which is available to authorized users.